Perbandingan Pelaksanaan Audit Program Bimbingan dan Konseling Komprehensif pada Tiga SMK - Rima Hazrati; Herdi Herdi; Khilda Wulidatin Noor (Jurnal Psikoedukasi dan Konseling, 2022)
Abstract: This study aims to compare program audits and the results of counseling services in three vocational high schools. This research uses a descriptive method. The data collection technique used was a research observation sheet with five alternative answers. Researchers researched two public vocational schools and one private vocational school in Jakarta. The assessment results show that the audit of First state vocational school's comprehensive guidance and counseling program is in the Good Enough category with a score of 53%. At first Private vocational school, it was concluded that the comprehensive audit of the guidance and counseling program was in the Good category with a score of 78%. In a second state vocational school, it was concluded that the comprehensive audit of the counseling program was in the Good category with a score of 98%. Researchers suggest that school counselors and administrators work together and build exemplary communication. There needs to be supervision and assistance from the manager so that the counseling program implementation goes well.Abstrak: Penelitian ini bertujuan untuk membandingkan audit program dan hasil layanan BK di SMK. Penelitian ini menggunakan metode deskriptif. Teknik pengumpulan data yang digunakan berupa lembar observasi penelitian dengan 5 alternatif jawaban. Peneliti melakukan penelitian di dua SMK negeri dan satu SMK swasta di Jakarta. Hasil penilaian menunjukkan bahwa audit program bimbingan dan konseling komprehensif SMA Negeri A Jakarta termasuk dalam kategori Cukup Baik dengan skor 53%. Di SMK Swasta A disimpulkan bahwa audit komprehensif program bimbingan dan konseling termasuk dalam kategori Baik dengan skor 78%. Di SMKN Negeri B disimpulkan bahwa audit komprehensif program bimbingan dan konseling termasuk dalam kategori Baik dengan skor 98%. Peneliti menyarankan kepada konselor sekolah dan juga administrator untuk bekerja sama dan membangun komunikasi yang baik. Perlu adanya pengawasan dan juga pendampingan dari pengelola agar pelaksanaan program bimbingan dan konseling berjalan dengan baik.